2017
DOI: 10.1017/s1742758417000145
|View full text |Cite
|
Sign up to set email alerts
|

Strip-intercropping canola with annual alfalfa improves biological control of Plutella xylostella (L.) and crop yield

Abstract: The population density of the diamondback moth (DBM),Plutella xylostella(L.), the species diversity of its predators, parasitism on eggs, larvae and pupae, and associated yield of canola were evaluated in experimental plots where spring canola was grown either as a monoculture or strip-intercropped with annual alfalfa in the ratio of 3C:3A, 6C:3A and 9C:3A over a 2-year period. The egg density was significantly higher in monoculture than in intercrops. The highest and lowest densities of larvae and pupae of DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Strip intercropping can provide yield benefits for farmers beyond supporting reductions in resource concentration, enhanced natural predator communities and higher biological pest control (Liang et al, 2016; Ning et al, 2017). Economic benefits of strip intercropping are commonly measured in terms of land use efficiency or harvested yields (Noman et al, 2013; Tajmiri et al, 2017b; Yu et al, 2015; Zhou et al, 2013), and reports of yield losses for one of the crops involved are frequent (Noman et al, 2013; Ramalho et al, 2012; Tajmiri et al, 2017a, 2017b). Noteworthy, yield data for all crops used in the mixture are rarely reported or considered in intercropping studies.…”
Section: Discussionmentioning
confidence: 99%
“…Strip intercropping can provide yield benefits for farmers beyond supporting reductions in resource concentration, enhanced natural predator communities and higher biological pest control (Liang et al, 2016; Ning et al, 2017). Economic benefits of strip intercropping are commonly measured in terms of land use efficiency or harvested yields (Noman et al, 2013; Tajmiri et al, 2017b; Yu et al, 2015; Zhou et al, 2013), and reports of yield losses for one of the crops involved are frequent (Noman et al, 2013; Ramalho et al, 2012; Tajmiri et al, 2017a, 2017b). Noteworthy, yield data for all crops used in the mixture are rarely reported or considered in intercropping studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to develop new, natural control methods as an alternative to chemical products. One example of such a novel approach is the use of intercropping systems to minimize resistance to pesticides [20,87,88], reduce pest population densities [87][88][89][90], increasing the diversity and efficiency of natural enemies [61,[91][92][93][94][95][96][97] and to improve crop yield [61,88,97].…”
Section: Available Methods For the Control Of T Urticaementioning
confidence: 99%
“…Surface deposits on Taxus baccata L. (Taxaceae) needles removed by dipping in water had a detrimental effect on the total fecundity and oviposition period of T. urticae [148]. Many experimental studies have demonstrated that fragrances of phylogenetically distant plants are most effective in repelling certain pests on host plants [17,20,[95][96][97]. When selecting potentially pesticidal plant extracts, several properties should be considered, including the efficiency of low concentrations in controlling mites, and lack of toxicity to other animals, ensuring safe use in sustainable agriculture [17].…”
Section: Natural Properties Of Plantsmentioning
confidence: 99%
“…Many studies have shown that adding plant diversity to cropping systems, one of the main strategies of conservation biological control, can increase the lifespan of natural enemies and improve parasitism of pests in the laboratory or greenhouse (Araj, Wratten, Lister, & Buckley, ; Irvin & Hoddle, ; Jamont, Crépellière, & Jaloux, ) and in the field (see review by Andow, ; Berndt, Wratten, & Scarratt, ; Idris & Grafius, ; Lee & Heimpel, ; Leius, ; Tajmiri, Fathi, Golizadeh, & Nouri‐Ganbalani, ). Targeted use of appropriate plant species (reviewed in Landis, Wratten, & Gurr, ) can help to provide alternative or additional hosts or prey, plant‐derived food sources (e.g., pollen, floral and extrafloral nectar, honeydew) and shelter for natural enemies.…”
Section: Introductionmentioning
confidence: 99%